Answered

Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

Simplify the expression:

–3(–2h + 3) =


Sagot :

Answer:  6h - 9

=================================================

Explanation:

The outer term -3 is multiplied by every term inside

We get the following

  • -3 times -2h = 6h
  • -3 times 3 = -9

This means the original expression becomes 6h-9. I applied the distributive property.

-3(-2h+3)=6h-9
Because a negative times a positive equals a positive and a negative times a positive equals a negative